PENGARUH PENAMBAHAN SERBUK LOGAM/NON-LOGAM TERHADAP KEKUATAN DAN PERILAKU RAMBAT RETAK PADA SAMBUNGAN LEM EPOXY - Khairul Anam (Journal of Environmental Engineering and Sustainable Technology, 2015)
Epoxy adhesive has been used widely in automotive and aircraft industry because it has the characteristics of a good joint in the structure of the component. The addition of the powder material on epoxy adhesive affect to the crack propagation behavior on the joint. It also affects to the peel and shear strength of the joint. A real experimental study of peeling and tearing test was used in this study. It aims to determine the effect of the type of powder material on crack propagation behavior and also peel and shear strength of the adhesive joint. The independent variable of this study is without powder and with powders (aluminum, iron ore, silica). The dependent variable is the crack propagation behavior and peel and shear strength. The results of the investigation shown that the addition of powder material either metal or non-metal on the epoxy adhesive joint affect on the maximum force and the displacement. In addition, it can also increase the peel and shear strength. In the peeling test, mixture of adhesive and cohesive fracture was occurred. And in the tearing test, fracture adhesive was dominated.